A review on marine plastisphere: biodiversity, formation, and role in degradation - Yuhui Du; Xinbei Liu; Xusheng Dong; Zhiqiu Yin (Computational and Structural Biotechnology Journal, 2022)
The pollution of plastic waste has become an increasingly serious environmental crisis. Recently, plastic has been detected in various kinds of environments, even in human tissues, which is an increasing threat to the ecosystems and humans. In the ocean, the plastic waste is eventually fragmentized into microplastics (MPs) under the disruption of physical and chemical processes. MPs are colonized by microbial communities such as fungi, diatoms, and bacteria, which form biofilms on the surface of the plastic called “plastisphere”. In this review, we summarize the studies related to microorganisms in the plastisphere in recent years and describe the microbial species in the plastisphere, mainly including bacteria, fungi, and autotrophs. Secondly, we explore the interactions between MPs and the plastisphere. The depth of MPs in the ocean and the nutrients in the surrounding seawater can have a great impact on the community structure of microorganisms in the plastisphere. Finally, we discuss the types of MP-degrading bacteria in the ocean, and use the “seed bank” theory to speculate on the potential sources of MP-degrading microorganisms. Challenges and future research prospects are also discussed.